The Effectiveness of the Inclusion of Governance as a Part of the Binding Articles of Association (The International Journal for Scientific Research, 2024)
This study investigates the efficacy of introducing governance as binding articles in the Articles of Association (AOA) of family businesses in Saudi Arabia, given the legislative reforms provided by the new Saudi Companies Law of 2022. The research points out that advantages will be brought by such enhanced transparency, accountability, and professional management practices, bringing family businesses up to international standards. Despite challenges such as resistance from family members, implementation complexity, and balancing traditional values with modern governance, the reforms provide substantial advantages. The case study of Saudi stock market companies illustrates the positive impact of phased governance reforms. Recommendations for successful implementation include engaging family members, leveraging external advisors, developing clear governance articles, providing training, and continuous monitoring. In all, these reforms serve as a giant stride toward ensuring that there is a strong, transparent, and sustainable business environment. This guarantees the long-term success and competitiveness of family businesses in Saudi Arabia.
Keywords: Governance; Family Businesses; Saudi Arabia; Articles of Association; Legislative Reforms